Training on the Improved NextGen Approach (PyCPT2.8) for Seasonal and Subseasonal Forecasting with the Ethiopian Meteorological Institute - Grossi, Amanda; Mason, Simon J. (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
New AICCRA-supported state-of-the-art forecasting systems are enabling regional and national meteorological agencies to generate timely and decision-relevant climate information for their agricultural sectors. Being able to generate and have access to reliable, location-specific forecasts enables the kinds of tailored advisories that farmers as well as staff from humanitarian and development agencies need for planning and supporting agricultural growth and resilience. It also enables anticipatory action in advance of emergencies. Towards the AICCRA project’s vision of actualizing a climate-smart African future driven by science and innovation in agriculture, the technical training on PyCPT immediately followed a workshop organized by the World Food Programme (WFP) in partnership with the IRI and EMI on anticipatory action trigger design, financing arrangements, and evidence generation in Ethiopia. This complementary workshop and initiative through WFP aimed to strengthen national capacities and systems for climate risk management, based on the generation, use and integration of tailored climate forecasts (such as those generated with PyCPT) and triggers into an Anticipatory Action Plan (AAP) including forecast-based finance (FbF) against drought. As such, the AICCRA-supported workshop in tandem with the AAP efforts through the WFP represent an important joint effort towards moving beyond access of climate information to advancing its use in decision-making, aligned with the goals of AICCRA Additional Finance (AF).